2017
DOI: 10.15406/mojwh.2017.04.00075
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Thyroid Dysfunction among Pregnant Women with Bad Obstetrical History

Abstract: Background: Subclinical maternal thyroid dysfunction adversely affects the obstetrical outcome. Treatment of subclinical hyper or hypothyroidism clearly improves the pregnancy outcome. Therefore screening of thyroid function in pregnancy is the need of time.Objective: To determine the frequency of subclinical thyroid dysfunction among pregnant women with bad obstetrical history Design: Cross sectional studySampling technique: Non-probability convenient sampling Materials and methods:This study was done at Choh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A prevalence as high as 65% has been recorded, while other studies show a low frequency of just <2%. 13,17,18 Western studies reported low frequency as compared to studies conducted in this part of the world. It may be because of the high prevalence of iodine deficiency in our region.…”
Section: Discussionmentioning
confidence: 94%
“…A prevalence as high as 65% has been recorded, while other studies show a low frequency of just <2%. 13,17,18 Western studies reported low frequency as compared to studies conducted in this part of the world. It may be because of the high prevalence of iodine deficiency in our region.…”
Section: Discussionmentioning
confidence: 94%